Evaluation of the Effectiveness of Treatment with Dexamethasone Intravitreal Implant in Cystoid Macular Edema Secondary to Retinal Vein Occlusion. (2nd August 2018) - Donati, Simone; Gandolfi, Carlo; Caprani, Simona Maria; Cattaneo, Jennifer; Premoli, Laura; Azzolini, Claudio
Abstract : Purpose. To evaluate retinal functional improvement by means of visual acuity and retinal sensibility examination after intravitreal dexamethasone implant in patients affected by cystoid macular edema secondary to retinal vein occlusion. Methods. Twenty-six consecutive patients affected by retinal vein occlusion complicated by cystoid macular edema were enrolled in this prospective interventional study. All patients underwent a baseline complete ophthalmological evaluation as well as retinal angiography, OCT examination, and microperimetry evaluation. Each patient was treated with intravitreal injection of a long-term steroid implant (Ozurdex, Allergan). Follow-up evaluations were performed at months 1, 3, and 6 and completed by OCT and MP1 examination. Clinical data underwent statistical analysis. Results. Baseline functional evaluation showed mean visual acuity of 0, 63±0, 42 LogMAR and retinal sensitivity of 7, 93±4, 73 dB (mean±standard deviation); after treatment, at day 30 we found, respectively, 0, 43±0, 38 LogMAR (p<0.05, compared to baseline) and 10, 15±4, 410 dB (p<0.05); at day 90, we found 0, 44±0, 32 (p<0.05) and 9.61±4, 29 dB (p<0.05); at day 180, we found 0, 41±0, 31 (p<0.05) and 9, 95±3, 79 dB (p<0.05). Fixation pattern improved significantly (p<0.05), showing a stable fixation in 30% of patients at baseline, increasing to 77% of patients at day 180. Baseline morphological evaluation showed a central retinal thickness (CRT) of 398, 21±181, 65  μ m after treatment; we found a CRT of 222, 64±95, 21  μ m at day 30 (p<0.05, compared to baseline), 307, 50±120, 25  μ m (p<0.05) at day 90, and 294, 93±135, 86  μ m (p<0.05) at day 180. About 15, 3% patients showed already at month 3 a recurrence of macular edema. They underwent a retreatment before month 6 as for treatment guidelines. Conclusion. Our detailed analysis showed the significative increase in retinal function in the early phases of the follow-up. Retinal sensibility showed a stronger correlation than VA in macular edema reabsorption, better underlying the progressive functional recovery and increase in quality of vision and life for the patients. This trial is registered with ClinicalTrials.govNCT03559491 .